2021
DOI: 10.3390/biom11101538
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic Potential of VEGF Mimetic Peptides for the Biofunctionalization of Collagen/Hydroxyapatite Composites

Abstract: Currently, the focus on bioinspired concepts for the development of tissue engineering constructs is increasing. For this purpose, the combination of collagen (Coll) and hydroxyapatite (HA) comes closest to the natural composition of the bone. In order to confer angiogenic properties to the scaffold material, vascular endothelial growth factor (VEGF) is frequently used. In the present study, we used a VEGF mimetic peptide (QK) and a modified QK-peptide with a poly-glutamic acid tag (E7-QK) to enhance binding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…Currently, we developed collagen/hydroxyapatite composites with good angiogenic properties by incorporating VEGF-mimetic peptides [36]. However, a cell type with proangiogenic properties could further support construct endothelialization in situ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, we developed collagen/hydroxyapatite composites with good angiogenic properties by incorporating VEGF-mimetic peptides [36]. However, a cell type with proangiogenic properties could further support construct endothelialization in situ.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the functionality of differently conditioned iMSCs secretomes also in the 3D-culture, sprouting assays with HUVEC spheroids were performed within collagen/hydroxyapatite (coll/HA) composite scaffolds. We described the generation of these scaffolds in a previous work [36]. HUVEC spheroids were incorporated into coll/HA scaffolds and incubated in the presence of differently pre-conditioned iMSCs secretomes (IFN-H, IFN-N, CO-H, and CO-N groups).…”
Section: Sprouting Assays By Huvec Spheroids Seeded On 3d Collagen/hy...mentioning
confidence: 99%
“…This led scientists to explore techniques which would promote and accelerate rapid host capillary ingrowth upon implantation such as functionalization of scaffolds with angiogenic growth factors [73][74][75][76][77]. Alternatively, scaffold design i.e., surface topography, porosity, pore size and pore interconnectivity are other well-known factors to affect vascular cell behavior and degree of vascular invasion [78][79][80][81][82][83][84].…”
Section: Engineering Capillary Beds: Strategies For the Fabrication O...mentioning
confidence: 99%
“…The critical factor for survival and function of tissue-engineered bone after implantation is rapid access to adequate blood perfusion [ 11 ]. With this in mind, many researchers have focused on the use of pro-vascular growth-related factors to stimulate angiogenesis in the recipient region and on the ingrowth of tissue-engineered products [ 2 , 4 ]. However, studies have confirmed that the limit of human microvascular growth rate is about 5 μm/h in physiological state [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%